The Empty Stage in Edward Hopper’s Early Sunday Morning, Girlie Show, and Two Comedians - Philip Smith (European Journal of American Studies)
This paper seeks to argue that Edward Hopper’s Early Sunday Morning (1930), Girlie Show (1941), and Two Comedians (1966) all show interest in the ephemerality of stage art. These paintings, I argue, depend upon innovations and fashions in lighting and set design from Hopper’ era. These influences, I further contend, extend beyond the mechanical to the thematic; if these paintings resemble the stage, it is significant that the stages he depicts are vacant of actors or signify either a scene which is about to occur or one which has ended. By evoking the empty stage, Hopper’s work, I seek to demonstrate, invites meditations on the impermanence of stagecraft.